Secondary school students' perceptions of physics and interdisciplinary course combinations in Tanzania - Emmanuel Deogratias; Geoffrey Karugila; Jeford Mwiyahuzi (UNION : Jurnal Ilmiah Pendidikan Matematika, 2025)
This study is necessary because physics, a fundamental subject in STEM education, is often viewed as challenging and less relevant, resulting in decreased student enrolment and poor academic performance. This study aimed to: Examine students' attitudes and perceptions towards physics as a subject, including their interests, motivations, and challenges; investigate students' perceptions of combinations involving physics, such as Physics, Chemistry, and Mathematics (PCM) and Physics, Chemistry, and Biology (PCB), and how these perceptions influence their subject choices; and assess the impact of students' perceptions on their academic achievement in physics and physics-related combinations, including their performance, grades, and overall learning outcomes. A mixed-methods approach was employed, combining quantitative (questionnaires, n = 100) and qualitative (interviews) data collection methods. The results showed that 64% of students expressed interest in physics, but many found it difficult due to mathematical complexity and limited practical learning opportunities. Key factors shaping students' perceptions included peer influence, teaching methods, and career aspirations. Notably, students with positive perceptions of physics were more likely to choose science combinations like Physics, Chemistry, and Mathematics (PCM) and Physics, Chemistry, and Biology (PCB), often driven by career ambitions. The study's findings have significant implications for physics education and STEM career participation. The results indicate that students’ perceptions have a substantial impact on subject choices and academic achievement. This study contributes to the physics education literature by providing empirical evidence from the Tanzanian secondary school context on how students’ perceptions of physics influence interdisciplinary subject combination choices and academic achievement, thereby informing context-sensitive strategies to strengthen STEM participation.